(untitled) (Archives of Mechanics - Test, 2000)
Experimental results concerning cyclic tension tests performed on polyamid based - braiding samples and on usual samples machined of the same PA66 polyamid are presented. The measurements are thermomechanical: the temperature of the surface of the sample is recorded, resulting in the estimation of the intrinsic internal heat supply. The materials are exhibiting not only the classical viscoelastoplastic behaviour, but also thermomechanical effects of the Kelvin and Taylor-Farreen-Quinney type. Modelling based on a previously proposed constitutive formulation of cyclic viscoplastic isotropic behaviour is implemented.